Does checking lactic acid have any benefit in conditions other than sepsis?. Issue 6 (June 2018) - Ludwig, Jennifer; Cusack, Melinda; Davis, Brock; Finn, Kendra; Raber, Hanna; Sheridan, Ed
Abstract : EVIDENCE‐BASED ANSWER : A lactic acid level of 2.5 mmol/L or higher is associated with increased mortality in geriatric patients with trauma (SOR: C, retrospective case series). Higher lactic acid levels in patients with out‐of‐hospital cardiac arrest, in an intensive care unit (ICU), or with acute heart failure are associated with lower survival (SOR: C, prospective and retrospective case series).